INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM MELALUI BUDAYA RELIGIUS DI KELAS 5 SEKOLAH DASAR NEGERI 29 SEDAYU TAHUN PELAJARAN 2024-2025 - Lusi Lusi; Eliyah Eliyah; Poniam Poniam (CV. Adiba Aisha Amira, 2025)
This study aims to describe and explore: (1) the Islamic education values instilled through religious culture in Grade V of State Elementary School 29 Sedayu, (2) the process of internalizing Islamic education values through religious culture, and (3) the implications of this internalization for students’ religious attitudes and behaviors. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The data analysis involved several stages: data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results revealed that the Islamic education values internalized through religious culture included values of aqidah (faith), sharia (worship and religious practice), and akhlaq (morality). The internalization process was carried out through exemplary behavior, habituation, and reinforcement in various religious activities, such as collective prayer, Qur’an recitation, Friday charity (infaq), and the 5S habits (Smile, Greet, Salute, Polite, and Courteous). This internalization positively influenced students’ religious character, as reflected in their increased discipline in performing prayers, willingness to lead prayers or the call to prayer (adhan), politeness, mutual respect, and the ability to apply Islamic values in daily life.